A software radio architecture for linear multiuser detection. - Seskar, I.P (IEEE Journal on selected areas in communications)
The integration of multimedia services over wireless channels calls for provision of variable quality of service (QoS) requirements. While radio resource management algorithms (such as power control and call admission control) can provide certain levels of variability in QoS, an alternate approach is to use reconfigurable radio architectures to provide diverse QoS guarantees. We outline a novel reconfigurable architecture for linear multiuser detection, thereby providing a wide range of bit error rate (BER) requirements amongst the constituent receivers of the reconfigurable architecture. Specifically, we focus on achieving this dynamic reconfiguration via a software radio implementation of linear multiuser receivers. Using a unified framework for achieving this reconfiguration, we partition functionality into two core technologies [field programmable gate arrays (FPGA) and digital signal processor (DSP) devices] based on processing speed requirements. We present experimental results on the performance and reconfigurability of the software radio architecture as well as the impact of fixed point arithmetic (due to hardware constraints)